2022
DOI: 10.1021/acsami.2c08555
|View full text |Cite
|
Sign up to set email alerts
|

Ba1/3CoO2: A Thermoelectric Oxide Showing a Reliable ZT of ∼0.55 at 600 °C in Air

Abstract: Thermoelectric energy conversion technology has attracted attention as an energy harvesting technology that converts waste heat into electricity by means of the Seebeck effect. Oxide-based thermoelectric materials that show a high figure of merit are promising because of their good chemical and thermal stability as well as their harmless nature compared to chalcogenide-based state-of-the-art thermoelectric materials. Although several high-ZT thermoelectric oxides (ZT > 1) have been reported thus far, the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Because Ba 1/3 CoO 2 epitaxial films exhibit good electron transport properties in the in-plane direction, κ must be measured in the in-plane direction to extract ZT . Previously, we used the TDTR method to measure the out-of-plane κ of the Ba 1/3 CoO 2 epitaxial films with two different crystallographic orientations: a c -axis orientation and a 55°-inclined c -axis. , Using these two out-of-plane κ data, we extracted the in-plane κ theoretically . It is very important that the κ value of the freestanding Ba 1/3 CoO 2 single-crystalline film measured using the AC calorimetric method agrees well with the κ value of the Ba 1/3 CoO 2 epitaxial film measured using the TDTR method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Ba 1/3 CoO 2 epitaxial films exhibit good electron transport properties in the in-plane direction, κ must be measured in the in-plane direction to extract ZT . Previously, we used the TDTR method to measure the out-of-plane κ of the Ba 1/3 CoO 2 epitaxial films with two different crystallographic orientations: a c -axis orientation and a 55°-inclined c -axis. , Using these two out-of-plane κ data, we extracted the in-plane κ theoretically . It is very important that the κ value of the freestanding Ba 1/3 CoO 2 single-crystalline film measured using the AC calorimetric method agrees well with the κ value of the Ba 1/3 CoO 2 epitaxial film measured using the TDTR method.…”
Section: Resultsmentioning
confidence: 99%
“…Ba 1/3 CoO 2 exhibited metallic p-type conductivity up to 600 °C in air. Recently, we found that Ba 1/3 CoO 2 epitaxial films exhibit a large ZT of 0.11 at room temperature and 0.55 at 600 °C . These values are the highest among reliable oxide thermoelectric materials and are comparable to those of commercially available p-type PbTe and SiGe .…”
Section: Introductionmentioning
confidence: 83%
“…[12,13] For sustainable generation of the power required in practical environments, hybrid and multisource energy-harvesting technologies have attracted substantial attention for their ability to continuously harvest energy and increase power output. [14][15][16][17] Among the energy harvesting technologies that have been reported thus far, TEGs have a number of advantagesincluding simplicity, [18,19] minimal maintenance requirements, [20,21] low cost, [22,23] and reliability, [24,25] that make them a good solution for sustainable power supply from waste heat sources. [26,27] From micro-electronics to industrial furnaces, numerous types of waste heats ranging from room temperature to high temperature (>600 °C) can be recovered into electricity by thermoelectric power generators depending on the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among the energy harvesting technologies that have been reported thus far, TEGs have a number of advantages—including simplicity, [ 18,19 ] minimal maintenance requirements, [ 20,21 ] low cost, [ 22,23 ] and reliability, [ 24,25 ] that make them a good solution for sustainable power supply from waste heat sources. [ 26,27 ] From micro‐electronics to industrial furnaces, numerous types of waste heats ranging from room temperature to high temperature (>600 °C) can be recovered into electricity by thermoelectric power generators depending on the materials.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Such inorganic thermoelectric materials need a high-temperature process (≥600 °C) and basically possess rigid and hard characteristics leading to very limited flexibility even in thin films. [8][9][10][11] To apply TEDs for various heat sources with curved surfaces including human skins, pipes, vehicles, etc., thermoelectric materials should have high flexibility and can be processed at low temperatures. [12,13] Although conventional inorganic materials can be formed on a flexible substrate or elastomeric frame, the resulting bulky TED modules have a restriction in practical uses.…”
mentioning
confidence: 99%